Capacidade funcional de exercício em pacientes submetidos à eletroestimulação neuromuscular no pós-operatório de cirurgia cardíaca: um ensaio clínico randomizado - Cerqueira, Telma Cristina Fontes (2018)
Background: The Neuromuscular electrical stimulation (NMES) is a potential resource to be applied to patients in the immediate postoperative period of cardiothoracic surgery in order to avoid functional loss, which often occurs even during a short period of hospitalization in the Intensive Care Unit. Objective: To investigate the effects of NMES on functional exercise capacity in cardiac surgery patients in the immediate postoperative period. Methods: In this randomised, controlled, adult patients in the preoperative period of coronary artery bypass grafting and cardiac valve replacement were randomly assigned to two groups: a control group, subjected to the usual care of physical therapy, or intervention group, who underwent NMES in the rectus femoris and gastrocnemius, bilaterally, for 60 minutes, for up to 10 sessions. The primary outcome was distance walked, assessed through the Six-Minute Walk Test at postoperative day 5. Secondary outcomes were walking speed; blood lactate after effort; muscle strength, assessed through the extensor isometric strength, handgrip strength and Medical Research Council scale; electrical muscle activity of the rectus femoris; functional independence measure and quality of life, assessed through the Nottingham Health Profile, at baseline (preoperative) and postoperative period. Statistical analyses were performed with SPSS. The chi-square test, t-test, the analysis of variance and the effect size calculation were performed. Results: The analysis included 45 patients, 23 in the NMES group and 22 in the control. There was no statistically significant difference between groups on distance walked (95% IC, -83,51 to 52,79, p=0,080), or walking speed, muscular strength, electrical muscle activity, functional independence and quality of life. However, patients in the NMES group preserve the extensor strength, the electrical muscle activity, muscle strength assessed through Medical Research Council and blood lactate after the effort when compared to the rest. There was a decrease in handgrip strengh, functional independence and decline in mobility assessed through PSN, with no return to baseline values in 5PO, except for mobility in the NMES group, which presented a return to preoperative values. Conclusion: The use of NMES has no effect on functional exercise capacity in the cardiac surgery patients in the immediate postoperative period, but was associated with preservation of muscle strength, recruitment of rectus femoris motor units, and blood lactate after effort.